1998
DOI: 10.2307/1592698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Commercial Competitive Exclusion Culture (Preempt [Trademark]) on Mortality and Horizontal Transmission of Salmonella gallinarum in Broiler Chickens

Abstract: A commercial competitive exclusion (CE) culture (PREEMPT) was evaluated for its ability to decrease mortality during the first 10-12 days posthatch resulting from the causative agent of fowl typhoid, Salmonella gallinarum. In the first experiment, chicks provided the CE culture on day of hatch and challenged with 10(5) S. gallinarum on day 3 had a significant decrease in mortality compared with non-CE-treated S. gallinarum-challenged chicks in all four replicates. Mortality for control chicks when averaged acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 10 publications
0
25
0
3
Order By: Relevance
“…Hence, the early administration of 'good' bacteria for competitive exclusion has been proposed as a method to prevent undesirable infections. There are several reports on the capacity of live bacterial cultures (Callaway et al, 2008;Corrier et al, 1998;Nisbet et al,1998;Wagner et al, 2003) and probiotic organisms (Higgins et al, 2007;Higgins et al, 2008;Higgins et al, 2010;Patterson & Burkholder, 2003;Vicente et al, 2008) to reduce the colonization of the gastrointestinal tract of poultry by opportunistic pathogens. The current study showed that the dietary inclusion of Bacillus subtilis enhanced the birds' immunity against Newcastle disease and avian influenza.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Hence, the early administration of 'good' bacteria for competitive exclusion has been proposed as a method to prevent undesirable infections. There are several reports on the capacity of live bacterial cultures (Callaway et al, 2008;Corrier et al, 1998;Nisbet et al,1998;Wagner et al, 2003) and probiotic organisms (Higgins et al, 2007;Higgins et al, 2008;Higgins et al, 2010;Patterson & Burkholder, 2003;Vicente et al, 2008) to reduce the colonization of the gastrointestinal tract of poultry by opportunistic pathogens. The current study showed that the dietary inclusion of Bacillus subtilis enhanced the birds' immunity against Newcastle disease and avian influenza.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Despite these current limitations, the administration of spores as feed additives as opposed to vegetative cells clearly distinguishes Bacillus probiotics from other bacterial probiotic formulations and offers a number of clear advantages. These include low cost of production, ease of preparation, resistance to production processes, and extended shelf-life over a wide range of temperatures.The use of competitive exclusion agents in the poultry industry has been described extensively in the prevention of several diseases caused by different avian pathogens, including zoonotic bacteria (1,24,40). However, the relatively undefined composition of some products and the uncertainty regarding their exact mechanisms of action have raised several ethical issues.…”
mentioning
confidence: 99%
“…The use of competitive exclusion agents in the poultry industry has been described extensively in the prevention of several diseases caused by different avian pathogens, including zoonotic bacteria (1,24,40). However, the relatively undefined composition of some products and the uncertainty regarding their exact mechanisms of action have raised several ethical issues.…”
mentioning
confidence: 99%
“…infection models. Pascual et al noted complete exclusion by 21 days of S. enterica serovar Enteritidis when they used Lactobacillus salivarius in chickens (25), and Nisbet et al observed a significant decrease in mortality due to S. enterica serovar Gallinarum infection in chicks treated with a commercial probiotic mixture (23). La Ragione et al observed no beneficial effect on serovar Enteritidis fecal numbers or colonization of the intestine when they pretreated chickens with Lactobacillus johnsonii (21).…”
mentioning
confidence: 99%